Association of fibroblast growth factor 21 with oxidative stress and lipid profile in type 2 diabetes - R., Vineetha K.; K., Santha; R., Inmozhi; S., Periyasamy; G., Kanakasabai; K., Baskaran (International Journal of Research in Medical Sciences, 2020)
Background: Cardiovascular disease is the most prevalent cause of morbidity and mortality in diabetic patients. Fibroblast growth factor 21 (FBG 21) is an endocrine factor that regulates glucose and lipid metabolism, insulin resistance, and obesity. Blood levels of FGF21 are elevated in patients with atherosclerosis, macrovascular, and microvascular complications of diabetes, possibly due to a compensatory up regulation. Studies reported that FGF21 is an important regulator of mitochondrial and oxidative stress. The role of FGF21 in chronic diseases and the diminished oxidative stress observed with anti-diabetic therapy has been the target of new studies. Current study aimed to evaluate serum FGF21 levels and its association with oxidative stress and lipid profile levels in type 2 diabetic patients. Methods: 100 controls and 100 diabetic patients on oral hypoglycemic drugs between 35-55 years of age without any cardiac, renal, liver, and thyroid dysfunction were selected for this study. Oxidative stress (MDA), total antioxidant status (FRAP), and FGF21 were measured. FGF21 was analyzed by ELISA methods. Serum MDA was assessed by the method of Yagi serum total antioxidant status was measured by the method of Benzie et al. Results: FGF21 level was increased in diabetic patients compared with controls. There was a significant positive correlation of FGF21 with MDA (r=0.875, p<0.01) and negative correlation with FRAP observed (r= -0.867 p<0.01). There was also positive correlation of FGF21 with total cholesterol (r=0.499, p<0.01), triglycerides (r=0.648, p<0.01), LDL-cholesterol (r=0.337, p<0.01) and negative correlation with HDL-cholesterol (r= -0.172, p<0.05) were observed. Conclusions: Increased oxidative stress and decreased antioxidant status were observed in diabetics. This could be due to dyslipidemia and increased generation of free radicals. High levels of FGF21 observed in our study might represent its resistant state and the compensatory response to maintain metabolic homeostasis. Further studies are needed to explore the role of FGF21 as a novel marker in predicting cardiovascular risk in diabetic patients.